(untitled) (Journal of School Administration Research and Development, 2020)
The pandemic disrupted teacher professional learning (TPL). This essay discusses key areas to be addressed in the TPL organization in the fall. They include health and safety; accelerated learning; technology; socio-emotional health; and equity.